The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40201-016-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential of polyaniline modified clay nanocomposite as a selective decontamination adsorbent for Pb(II) ions from contaminated waters; kinetics and thermodynamic study

Abstract: BackgroundNowadays significant attention is to nanocomposite compounds in water cleaning. In this article the synthesis and characterization of conductive polyaniline/clay (PANI/clay) as a hybrid nanocomposite with extended chain conformation and its application for water purification are presented.MethodsClay samples were obtained from the central plain of Abhar region, Abhar, Zanjan Province, Iran. Clay was dried and sieved before used as adsorbent. The conductive polyaniline was inflicted into the layers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The EDX spectra of PAni/SF (Fig. b,c) further confirmed the introduction of chlorine (ClK α 2.8 keV) and nitrogen (NK α 0.53 keV) during the oxidative polymerization . It is worthy to note PAni is coated in the oxidized form and chlorine is incorporated as a dopant to keep the amine positive charge balanced.…”
Section: Resultsmentioning
confidence: 55%
“…The EDX spectra of PAni/SF (Fig. b,c) further confirmed the introduction of chlorine (ClK α 2.8 keV) and nitrogen (NK α 0.53 keV) during the oxidative polymerization . It is worthy to note PAni is coated in the oxidized form and chlorine is incorporated as a dopant to keep the amine positive charge balanced.…”
Section: Resultsmentioning
confidence: 55%
“…However, the adsorption capacity decreased when increasing the amount of MMT in the composite, which is explained by the tendency of clay particles to aggregate in the PANI matrix and, therefore, hinder the availability of active sites. In a study conducted by Piri et al [92], a polyaniline/clay nanocomposite was fabricated and tested for the removal of Pb(II) from aqueous solution. The surface characterization of the PANI/clay nanocomposite showed that the clay layers were flaked in the nanocomposite.…”
Section: Nanoclay/pani Nanocompositesmentioning
confidence: 99%
“…Among these methods, adsorption using chelating resins is considered one of the most efficient methods for water treatment owing to its low cost, flexibility in operation, and design compared to those of other methods. Many different materials have been used as adsorbents for the uptake of toxic substances from polluted water such as metal oxides, , activated carbon (AC), covalent organic frameworks (COFs), , metal organic frameworks (MOFs), , minerals (clay), inorganic nanomaterials, agriculture wastes, , graphene oxide (GO), , and polymers. , Most of these adsorbents have low selectivity and capacity. Therefore, it is important to remove toxic metals from contaminated water using cheap and efficient adsorbents.…”
Section: Introductionmentioning
confidence: 99%